Mahasiswa Versus Tugas: Prokrastinasi Akademik dan Conscientiousness - Surijah, Edwin Adrianta; Sia, Tjundjing (Faculty of Psychology, Universitas Surabaya, 2007)
The present study explores the correlation between postponing finishing school assignments, known as academic procrastination of students and their conscientiousness. Psychology students from the 2003-2006 intakes (N = 295) participated in this study. They finished three kinds of questionnaires (the author’s main scale, and two others for comparison, adapted from Aitken Procrastination Inventory and Big Five Inventory). Result from the main scale reveals a negative correlation (r = -0.627), which is supported by the other two tests. These results also propose that students havinga conscientious character, i.e. structured, perseverance, and good self-control tend to be prevented from procrastination. Penelitian ini mengungkap hubungan antara sifat menunda mengerjakan tugas atau prokrastinasi akademik pada para mahasiswa dan aspek conscientiousnessnya. Mahasiswa sebuah fakultas psikologi, angkatan 2003-2006 (N = 295) menjadi responden penelitian ini. Para partisipan mengisi 3 jenis skala (satu skala utama dari penulis, dan dua skala pembanding, adaptasi dari skala Aitken Procrastination Inventory dan Big Five Inventory.) Hasil pengujian menggunakan skala utama menunjukkan adanya hubungan negatif (r = -0.627), yang diperkuat oleh hasil pengujian skala pembanding. Hasil tersebut juga menyiratkan bahwa mahasiswa yang memiliki karakter conscientious yaitu terstruktur, tekun, serta memiliki kendali diri yang baik cenderung terhindar dari prokrastinasi.